On a Sustainable Future of the Earth's Natural Resources - Ramkumar, Mu (Springer Earth System Sciences,, 2013)
On a Sustainable Future of Earth's Natural Resources is divided into three sections, with individual chapters contributed by experts on different facets of the earth sciences, natural resources management and related issues. The first section focuses on the status of Earth's resources; land, water, biota and atmosphere. Reviews on the rate of exploitation and the need to conserve these resources for future sustenance are also covered in this section. The following section includes chapters elucidating environmental, ecological, climatological and anthropological pressures on sustained nourishment with the Earth's resources. The last section describes management practices, issues and  perspectives on sociological, legal, administrative, ICT and strategic efforts that need to be implemented in order to sustain our natural resources. This book covers a broad spectrum of the Earth's resources and sustenance, offering a comprehensive perspective on their past, present and future.